Effects of coated sodium butyrate on production performance, egg quality, serum biochemistry, digestive enzyme activity, and intestinal health of laying hens. Issue 1 (1st January 2021) - Miao, Sasa; Zhou, Wenting; Li, Huaiyu; Zhu, Mingkun; Dong, Xinyang; Zou, Xiaoting
Abstract: The present study was conducted to investigate the effects of coated sodium butyrate (CSB) on production performance, egg quality, serum biochemistry, digestive enzyme activity, intestinal health of laying hens. 720 hens at 52 weeks were assigned in five groups including basal diet (control) and a basal diet supplemented with 250, 500, 750, and 1000 mg/kg CSB for 8 weeks. The results showed that the 500 mg/kg CSB group increased laying rate but 500 and 750 mg/kg groups decreased feed conversion ratio ( p  < .05). At the fourth week, dietary CSB at more than or equal to 500 mg/kg level increased the Haugh unit ( p  < .01); At the eighth week, 500 and 1000 mg/kg CSB groups improved the eggshell strength, Haught unit and albumen height ( p  < .05). Dietary CSB administration except for the 250 mg/kg group increased the serum albumin and calcium and decreased the triglyceride content ( p  < .05). 500 and 750 mg/kg CSB groups increased the activities of trypsin and amylase in the pancreas and duodenum ( p  < .05). The groups of 500 and 750 mg/kg increased the villus height and villus height to crypt depth ratio (V/C) in the jejunum and ileum ( p  < .05). In the jejunum, at more than or equal to 500 mg/kg CSB groups increased the expressions of ZO-1 and Occludin ( p  < .05); In the ileum, 500 and 750 mg/kg CSB groups increased the expressions of claudin-1 and occludin and ZO-2 ( p  < .05). Conclusively, dietary supplementation of CSB can improve egg production, egg quality, digestive enzyme activity and present a positive effect on improving villi and intestinal mechanical barrier function. HIGHLIGHTS: A significant improvement in production performance and egg quality was observed in birds fed diet with coated sodium butyrate. Administration of coated sodium butyrate enhanced protein and mineral availability and lipid metabolism of serum. Supplementation of coated sodium butyrate presented a positive impact on regulating intestinal health.